Computational methods for agricultural research : advances and applications - Prado, Hercules Antonio do.; Luiz, Alfredo Jose Barreto, 1963-; Filho, Homero Chaib (Hershey, PA : Information Science Reference, 2011)
"This book brings computing solutions to ancient practices and modern concerns, sowing the seeds for a sustainable, constant food supply, utilizing cutting-edge computational techniques"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Agriculture -- Research -- Data processing; Agricultural informatics